2019
DOI: 10.1055/s-0038-1676287
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Renal Stones in Severely Disabled Children with Epilepsy Treated with Topiramate

Abstract: Purpose This study was aimed to assess the accurate incidence of renal stones in severely disabled children treated with topiramate (TPM). Method We reviewed the medical records of severely disabled children with epilepsy under 15 years old who underwent radiological examinations to investigate urinary stones. The study enrolled 26 patients who were divided into two groups. One group had been treated with TPM for at least 1 year and the other had not been treated with TPM, zonisamide, acetazolamide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
1
6
0
2
Order By: Relevance
“…Two studies tried to determine the accurate incidence of TPM-induced urolithiasis in the pediatric population through comparing the incidence of urolithiasis between children with disability using TPM for management of refractory epilepsy versus a control group of similar children not using TPM. They showed similar results, with an incidence of urolithiasis significantly higher in the TPM group versus the no TPM group (60% vs 0% and 54.6% vs 0%) [86,87]. Furthermore, an open-label extension study from two studies (phase 1 and phase 3) in 284 infants < 2 years old with refractory partial-onset seizures treated with TPM (only 135 infants completed the open-label extension study) was published in 2011 and showed that one of the treatmentemergent adverse events found was nephrolithiasis in 18 of the 135 patients (13.3%) [93].…”
Section: Topiramatesupporting
confidence: 52%
See 4 more Smart Citations
“…Two studies tried to determine the accurate incidence of TPM-induced urolithiasis in the pediatric population through comparing the incidence of urolithiasis between children with disability using TPM for management of refractory epilepsy versus a control group of similar children not using TPM. They showed similar results, with an incidence of urolithiasis significantly higher in the TPM group versus the no TPM group (60% vs 0% and 54.6% vs 0%) [86,87]. Furthermore, an open-label extension study from two studies (phase 1 and phase 3) in 284 infants < 2 years old with refractory partial-onset seizures treated with TPM (only 135 infants completed the open-label extension study) was published in 2011 and showed that one of the treatmentemergent adverse events found was nephrolithiasis in 18 of the 135 patients (13.3%) [93].…”
Section: Topiramatesupporting
confidence: 52%
“…Thus, TPM has become one of the most frequently prescribed drugs in the USA, ranking among the top 50 most prescribed drugs [85]. TPM has been long known for its lithogenic effect through the metabolic changes induced by this drug [86][87][88][89][90][91][92][93]. A systematic review published in 2013 showed that the overall annual incidence of symptomatic nephrolithiasis with TPM usage was 2.1% [94]; however, the incidence of nephrolithiasis in the pediatric population ranged from 4.2% to 60% (Table 3).…”
Section: Topiramatementioning
confidence: 99%
See 3 more Smart Citations